2006
DOI: 10.1002/ana.20766
|View full text |Cite
|
Sign up to set email alerts
|

The human immunodeficiency virus reduces network capacity: Acoustic noise effect

Abstract: Increased acoustic noise (AN) during working memory (WM) leads to increased brain activation in healthy individuals, and may have greater impact in human immunodeficiency virus (HIV) patients. Compared to controls, HIV subjects showed reduced AN-activation and lower neuronal marker Nacetylaspartate in prefrontal and parietal cortices. Competing use of the WM network between AN and cognitive load showed lower dynamic range of the hemodynamic responses in prefrontal and parietal cortices in HIV patients. These f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 61 publications
4
19
0
Order By: Relevance
“…At baseline, HIV participants showed a reorganized neural network compared to SN participants even on the relatively simple 1‐back task, with greater activation in the medial and lateral frontal regions, but lesser activation in brainstem and bilateral cingulate gyri, which are consistent with previous studies of WM and sustained attention tasks in HIV participants 20, 22, 23, 41. Similarly, on the 2‐back task, the greater activation in bilateral medial frontal regions and the right precentral gyrus is also consistent with greater usage of the reserve attention network, or increased attentional modulation for this more‐difficult task in HIV patients 21, 24…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…At baseline, HIV participants showed a reorganized neural network compared to SN participants even on the relatively simple 1‐back task, with greater activation in the medial and lateral frontal regions, but lesser activation in brainstem and bilateral cingulate gyri, which are consistent with previous studies of WM and sustained attention tasks in HIV participants 20, 22, 23, 41. Similarly, on the 2‐back task, the greater activation in bilateral medial frontal regions and the right precentral gyrus is also consistent with greater usage of the reserve attention network, or increased attentional modulation for this more‐difficult task in HIV patients 21, 24…”
Section: Discussionsupporting
confidence: 86%
“…On fMRI, both groups showed typical robust activation patterns during the 1‐back and 2‐back WM tasks20, 22 (Figs 4 and 5). On the 1‐back task, HIV participants showed greater activation than SN controls (FDR corrected, p  < 0.0001) in frontal regions, with local maxima at the left cingulate gyrus (Brodmann's area [BA] 24), left medial frontal gyrus (BA 6), and right middle frontal gyrus (BA 9; Supplementary Table 1).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Further, functional neuroimaging studies have shown that individuals with the met allele do better on neuropsychological tests of executive functioning and working memory, which presumably assess prefrontal cortical function (Egan et al 2001;Goldberg et al 2003;Mattay et al 2003). Such findings are particularly relevant to HIV, as a recent neuroimaging study suggested reduced neural processing capacity in working memory networks in those with HIV (Tomasi et al 2006). …”
Section: Catechol-o-methyl-transferase (Comt)mentioning
confidence: 99%
“…BR theory views premorbid variables, such as VIQ, educational attainment, or brain size, as important factors explaining the wide variation in functional outcomes after brain disease or injury across patients with similar structural deficits. It has been invoked by investigators studying HIV/AIDS (Stern et al, 1996;Tomasi et al, 2006), dementia (Spitznagel and Tremont, 2005;Zhang et al, 1990), Alzheimer's Disease (Bennett et al, 2003;Scarmeas et al, 2004;Stern et al, 1994), multiple sclerosis (Cader et al, 2006), and other disorders (Farmer et al, 2002;Kesler et al, 2003;Ropacki et al, 2003), as well as normal aging .…”
Section: Introductionmentioning
confidence: 99%